A novel and clean technique for the one-pot production of green chemical ?-valerolactone from furfural using bifunctional H3PW12O4/UiO-66 catalyst: Pervaporation membrane reactor - Mutlu, Bade; Unal, Buse; Unlu, Derya (Elsevier Sci Ltd, 2024)
This study focuses on the synthesis of gamma-valerolactone (GVL) from furfural using a bifunctional H3PW12O4UiO-66 catalyst. The membrane was prepared using PBI polymer. H3PW12O4-UiO-66 catalysts with different amounts of H3PW12O4 were synthesized. The catalytic activity of these synthesized catalysts was investigated in pervaporation membrane reactor to obtain GVL from furfural and the catalyst containing 2 g of H3PW12O4 was identified as the optimum catalyst. After determining the optimum catalyst, the effect of temperature, molar feed ratio, and catalyst concentration on the reaction and separation performance was investigated. The optimum values were determined as 90 degrees C, molar feed ratio 10 and 6 g/L catalyst concentration by evaluating both reaction and separation performance. The performance of the pervaporation membrane reactor (PVMR) was compared with a batch reactor operated under the same conditions. In the batch reactor operating at 90 degrees C, molar feed ratio of 10, and 6 g/L catalyst concentration, a 65% furfural conversion and 51% GVL yield were obtained, whereas the PVMR achieved 100% furfural conversion and 94.21% GVL yield. This comparison demonstrates the improved efficiency of the PVMR in increasing conversion and yield compared to the traditional batch reactor. The obtained conversion and yield values under the investigated operating conditions highlight the proposed process as a promising alternative for the production of GVL from furfural.
Keywords: Bifunctional catalyst; Furfural; GVL; Pervaporation membrane reactor